Dynamic Scoring for Quran Memorization Assessment in Journey of Ayat Educational Game Using the Fuzzy Tsukamoto Algorithm - Aysyah Noor Shobah; Rio Andriyat Krisdiawan; Rio Priantama (Media Jurnal Informatika, 2026)
Conventional Qur’an memorization assessment in Madrasah Diniyah Takmiliyah (MDT) often relies on direct teacher evaluation and simple correct-or-wrong scoring, which may not fully represent students’ memorization performance. At MDT An-Nidzom, preliminary assessment showed that students experienced difficulties in completing verse fragments of selected short surahs. Objective: This study aimed to develop Journey of Ayat, an Android-based educational game, and implement the Fuzzy Tsukamoto algorithm as a dynamic scoring mechanism for Qur’an memorization assessment. Methods: The study employed a Research and Development approach using the Game Development Life Cycle. The scoring model used three input variables, namely correct answers, completion time, and remaining lives, to generate a final score. The system was evaluated through black-box testing, white-box testing, Fuzzy Tsukamoto calculation validation, User Acceptance Testing, and pretest-posttest analysis involving 40 students and one teacher at MDT An-Nidzom. Results: The developed system provided memorization practice, gameplay interaction, score calculation, and teacher monitoring. The Fuzzy Tsukamoto calculation was consistent with manual calculation, with an error value of 0.00 in the validation scenario. Black-box testing showed that the main features operated as expected, while white-box testing produced a cyclomatic complexity value of 2. The UAT results indicated very feasible ratings of 92.00% from the teacher and 89.06% from students. The mean memorization score increased from 62.75 to 70.00, and the Wilcoxon signed-rank test showed a statistically significant difference in the observed sample (p = 0.0237). Conclusion: Journey of Ayat is feasible as a supporting medium for Qur’an memorization practice and preliminary assessment. However, further studies involving broader samples, control-group comparison, and oral recitation assessment are needed to strengthen evidence of learning effectiveness.